(3EJMGa GdSGdc HQhGI ehWC eGdcs - (3GHf fGUQ GdOjf , eMeO Hf YHO Gddg Hf eMeO Hf CMeO Hf eLGgO, TeS GdOjf CHh HcQ,J (B842 (3g` s ((3eMeO Hf eMeO CH MGeO Hf MSf Hf Ydj GdeGdcj GdHcQj GdNdjdj Gdecj s)
(3ChdgG (B:s
(3hHYO aEf HYV Cgd GdSfI hNOGegG hef fTC Hjf CFeJgG hCYdGegG bUO efi hGdJeS , PcQQhGI ehWC GdEeGe eGdc Hf CfS GdPjf dbhI QVi Gddg Yfg hSeYhG efg cJGHg GdehWC s
(3BNQgG (B:s
(3hfSCd GdaYGd deG jQjO hdG QGO deG CQGOg Cf jdWa HfG ai GdOGQjf eY fhGd GdMSfi hRjGQI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B81 - (3U(B158s
(3GfXQ GdbSe GdChd HQbe (B5s
(3fSNI KGfjI hGdfSNI HQhGjI GdfGSN bQCgG eTGagI Ydi GdTjN CHj GdNjQ eMeO bWH GdOjf GdNjVQi Ydi GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B237 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B236s
Keywords: (3GdJGQjNs